Tinjauan Yuridis Terhadap Tindak Pidana Penggelapan Dalam Jabatan - Ikram, Muhammad; Rahman, Sufirman; Arsy, Muhammad (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2022)
This study aims to determine how the application of material criminal law to the criminal offence of embezzlement in and how the legal considerations by judges against the criminal offence of embezzlement in office in decision number 412/Pid.B/2018/PN.Mks. The research method used is normative research. The results showed that the application of material criminal law by the Panel of Judges against the perpetrator of the crime of embezzlement in office which stated that the defendant was legally and convincingly guilty of committing the crime of embezzlement in office as regulated in Article 374 of the Criminal Code because the perpetrator committed a criminal act. Legal considerations by the Panel of Judges in imposing a sentence in Decision Number 412/Pid.B/2018/PN.Mks are considered inappropriate. Because the decision of the Panel of Judges is not in accordance with the decision applied. In accordance with the facts, the defendant only has the status of an ordinary employee who cannot be said to be a position in accordance with the decision of the Panel of Judges in Article 374 of the Criminal Code applied by the Panel of Judges. Recommendations and this research are that it is better to be able to impose a punishment that is appropriate / commensurate with the criminal offence committed in order to create the expected legal objectives, namely: Justice, Certainty, and Legal Benefit based on God Almighty. Abstrak:Penelitian ini bertujuan untuk mengetahui Bagaimana penerapan hukum pidana materil terhadap tindak pidana penggelapan dalam dan Bagaimana pertimbangan hukum oleh hakim terhadap tindak pidana penggelapan dalam jabatan dalam putusan nomor 412/Pid.B/2018/PN.Mks. Metode penelitian yang di gunakan adalah Penelitian normatif. Hasil penelitian menunjukkan bahwa Penerapan hukum pidana materiil oleh Majelis Hakim terhadap pelaku tindak pidana penggelapan dalam jabatan yang menyatakan terdakwa secara sah dan meyakinkan bersalah melakukan tindak pidana penggelapan dalam jabatan sebagaimana diatur dalam pasal 374 KUHPidana karena pelaku melakukan tindak pidana.. Pertimbangan Hukum oleh Majelis Hakim dalam menjatuhkan hukuman dalam Putusan Nomor 412/Pid.B/2018/PN.Mks dinilai kurang tepat. Karena putusan Majelis Hakim tidak sesuai dengan putusan yang di terapkan. Sesuai dengan Fakta – fakta yang ada terdakwa hanya memiliki status karyawan biasa yang tidak bisa dikatakan suatu jabatan yang sesuai dengan putusan Majelis Hakim pasal 374 KUHPidana yang di terapkan oleh Majelis Hakim. Rekomendasi dan penelitian ini yaitu sebaiknya dapat menjatuhkan pidana yang sesuai/setimpal dengan tindak pidana yang dilakukan agar tercipta tujuan hukum yang diharapkan, yaitu : Keadilan, Kepastian, dan Kemanfaatan Hukum berdasarkan Tuhan Yang Maha Esa